Reducing aerodynamic drag by adopting a novel road-cycling sprint position - Merkes, P. F. J.; Menaspà, P.; Abbiss, C. R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To assess the influence of seated, standing, and forward-standing cycling sprint positions on aerodynamic drag (CdA) and the reproducibility of a field test of CdA calculated in these different positions. Methods: A total of 11 recreational male road cyclists rode 250 m in 2 directions at around 25, 32, and 40 km/ and in each of the 3 positions, resulting in a total of 18 efforts per participant. Riding velocity, power output, wind direction and velocity, road gradient, temperature, relative humidity, and barometric pressure were measured and used to calculate CdA using regression analysis. Results: A main effect of position showed that the average CdA of the 2 d was lower for the forward-standing position (0.295 [0.059]) compared with both the seated (0.363 [0.071], P?=?.018) and standing positions (0.372 [0.077], P=.037). Seated and standing positions did not differ from each other. Although no significant difference was observed in CdA between the 2 test days, a poor between-days reliability was observed. Conclusion: A novel forward-standing cycling sprint position resulted in 23% and 26% reductions in CdA compared with a seated and standing position, respectively. This decrease in CdA could potentially result in an important increase in cycling sprint velocity of 3.9-4.9 km/h, although these results should be interpreted with caution because poor reliability of CdA was observed between days.